Novel insights into genetic susceptibility for colorectal cancer from transcriptome-wide association and functional investigation - Chen, Zhishan; Song, Wenqiang; Shu, Xiao-Ou; Wen, Wanqing; Devall, Matthew; Dampier, Christopher; Moratalla-Navarro, Ferran; Cai, Qiuyin; Long, Jirong; Van Kaer, Luc; Wu, Lan; Huyghe, Jeroen R; et al. (Journal of the National Cancer Institute, 2024)
BACKGROUND: Transcriptome-wide association studies have been successful in identifying candidate susceptibility genes for colorectal cancer (CRC). To strengthen susceptibility gene discovery, we conducted a large transcriptome-wide association study and an alternative splicing transcriptome-wide association study in CRC using improved genetic prediction models and performed in-depth functional investigations. METHODS: We analyzed RNA-sequencing data from normal colon tissues and genotype data from 423 European descendants to build genetic prediction models of gene expression and alternative splicing and evaluated model performance using independent RNA-sequencing data from normal colon tissues of the Genotype-Tissue Expression Project. We applied the verified models to genome-wide association studies (GWAS) summary statistics among 58 131 CRC cases and 67 347 controls of European ancestry to evaluate associations of genetically predicted gene expression and alternative splicing with CRC risk. We performed in vitro functional assays for 3 selected genes in multiple CRC cell lines. RESULTS: We identified 57 putative CRC susceptibility genes, which included the 48 genes from transcriptome-wide association studies and 15 genes from splicing transcriptome-wide association studies, at a Bonferroni-corrected P value less than .05. Of these, 16 genes were not previously implicated in CRC susceptibility, including a gene PDE7B (6q23.3) at locus previously not reported by CRC GWAS. Gene knockdown experiments confirmed the oncogenic roles for 2 unreported genes, TRPS1 and METRNL, and a recently reported gene, C14orf166. CONCLUSION: This study discovered new putative susceptibility genes of CRC and provided novel insights into the biological mechanisms underlying CRC development.
Keywords: celogenomová asociační studie; Transcriptome; jednonukleotidový polymorfismus; Genome-Wide Association Study; Colorectal Neoplasms; Polymorphism, Single Nucleotide; Genetic Predisposition to Disease; Repressor Proteins; Humans; kolorektální nádory; lidé; RNA; represorové proteiny; genetická predispozice k nemoci; transkriptom